2020
DOI: 10.5114/fmpcr.2020.92500
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early menopause in Bangladesh

Abstract: Background. Early menopause is a risk factor for several health-related problems of women. No single study was available in literature to determine the associated factors for early menopause in Bangladesh. Objectives. The aim of this study was to determine the prevalence and factors associated with early menopause in Bangladesh. Material and methods. Data was extracted from the nationally representative Bangladesh Demographic and Health Survey (BDHS) 2014. This data was collected from 17,863 married Bangladesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…A pan Indian study discovered that (Pallikadavath et al, 2016) residential and literacy status, duration of breast feeding of child, and husband’s awareness about the menopausal status of spouse were significant predictors of some of the menopausal symptoms. This study is in the same line with the results by Ali et al (2020) who reported that the Bangladeshi women who were not using any contraceptive method had a 3.62-times higher chance of early menopause than who were using a contraceptive method. In accordance with the idea that OCPs postpone oocyte depletion, several studies have found that women who took OCPs experience natural menopause at a later age (Zsakai et al, 2015; Lujan-Barroso et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…A pan Indian study discovered that (Pallikadavath et al, 2016) residential and literacy status, duration of breast feeding of child, and husband’s awareness about the menopausal status of spouse were significant predictors of some of the menopausal symptoms. This study is in the same line with the results by Ali et al (2020) who reported that the Bangladeshi women who were not using any contraceptive method had a 3.62-times higher chance of early menopause than who were using a contraceptive method. In accordance with the idea that OCPs postpone oocyte depletion, several studies have found that women who took OCPs experience natural menopause at a later age (Zsakai et al, 2015; Lujan-Barroso et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The age at which menopause begins did not significantly correlate with marital status in a research done in Greece [ 31 ]. According to a different research, divorced and bereaved women are more likely to have early menopause [ 27 , 32 ]. Ovulation ceases during pregnancy, therefore the more births and pregnancies a woman has, the more eggs she retains, which helps prevent early menopause in women.…”
Section: Discussionmentioning
confidence: 99%
“…All these variables were considered for the bivariate analysis, and further for the regression analysis. The selected variables were chosen for the current study as these were found to be significantly associated with menopausal age in previous studies (Ali et al, 2020;Awal et al, 2019;Ceylan & Özerdoğan, 2015;Li et al, 2012;Wang et al, 2018).…”
Section: Study Instrument and Measuresmentioning
confidence: 99%
“…Of the genetic factors, mother's age at menopause has been reported to have an influence on women's early or late menopause (Ceylan & Özerdoğan, 2015). Socioeconomic factors including religion, residence, age at marriage, BMI (Awal et al, 2019), education (Ali et al, 2020;Awal et al, 2019), occupation (Ahuja, 2016), and lower socioeconomic status (Canavez et al, 2011;Li et al, 2012) in general has been reported as the significant determinants of age at menopause in some previous studies. Women with lower education (Li et al, 2012;Pérez-Alcalá et al, 2013;Wang et al, 2018), separated, divorced and widowed (Ahmed et al, 2016), and underweight (Szegda et al, 2017;Tao et al, 2015;Wang et al, 2018) are more likely to experience early menopause.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation